Assessment of Service Quality of Academic Resources Center Rajamangala University Technology Isan, Nakhon Ratchasima - ชูพุทธพงษ์ กัญญาภัทร (RMUTI Journal Humanities and Social Sciences, 2019)
The Purpose of this independent study was to assess the quality service of the Academic Resources Center of Rajamangala University Isan, Nakhon Ratchasima using LibQUAL+TM concept which determined 3 service quality dimensions: emotion toward service, physical facilities, and Information control. Each dimension determined the service quality at 3 levels: minimum acceptable level, desirable level, and the services which were actually obtained. The gap scores of each level were defined as Zones of Tolerance, Service Adequacy, and Service superiority. The Study sample included 375 undergraduate students of Rajamangala University lsan in the academic year of 2016. Questionnaires were used to collect data which were then statistically analyzed using frequency, percentage, mean, and standard deviation. The findings revealed that all 3 service quality dimensions of the Academic Resources Center were at the moderately level ( = 5.91, = 6.27), and the desirable services were at the highest level ( = 6.54). The analysis of the gap scores indicated that the cores of the 3 service quality dimensions were at the acceptable level.